Sulfur-mediated transformation from osmium nanocrystals to single atoms for efficient alkaline hydrogen evolution reaction - Wendan Xue; Qixing Zhou; Pengfei Wang; Sijin Zuo; Fengxiang Li; Jiwei Jiang; Fan Mo; Chuan Yin; Gaolei Liu; Zhan Ban; Yuanyuan Wei; Wen An; et al. (Proceedings of the National Academy of Sciences, 2025)
Osmium (Os)-based catalysts, recognized for their unique chemical and electronic properties along with cost-effectiveness, hold great potential for the hydrogen evolution reaction (HER). However, their practical application has long been limited because pure Os exhibits excessively strong adsorption of intermediates and suffers from stability issues. Herein, we report the development of a highly stable catalyst achieved by implanting the sulfur (S) atom into the matrix, facilitating the transformation of Os nanocrystals into Os single atoms. The prepared atomically dispersed Os catalyst (Os-SA@SNC) demonstrates outstanding catalytic activity, requiring only a 13 mV overpotential to achieve a current density of 10 mA cm −2 in 1.0 M potassium hydroxide (KOH) solution, as well as the excellent durability. This performance surpasses that of commercial Pt/C and outperforms most of the reported state-of-the-art electrocatalysts. Theoretical simulations clarify the important role of S atoms in promoting the dispersion and diffusion of Os atoms. Moreover, density functional theory calculations indicate that S atoms adjust the local electronic structure of Os active sites, further facilitating the adsorption/dissociation of H 2 O and optimizing the hydrogen adsorption free energy (ΔG *H ), thereby accelerating the kinetics of both the Volmer and Heyrovsky steps in alkaline HER. This work revitalizes Os-based catalysts for energy conversion and paves the way for innovative HER catalyst design and application to contaminated soil/water remediation.